Curriculum Development of Anak Beragama Cinta Damai (ABCD) Program to Internalize the Value of Religious Moderation for Elementary School Students in West Java - Srie Mulyati (Indonesian Journal of Primary Education, 2024)
In the last 5 years, survey results show that religious harmony in West Java placed in the 10th lowest rank in Indonesia. Anak Beragama Cinta Damai or ABCD program aims to strengthen the process of internalizing the values of religious moderation at the elementary school (SD/MI) level towards the value of tolerance using a humanistic approach by involving students directly through a series of learning programs. This study uses a qualitative approach, namely literature review. The form of this program is advocacy and value habituation activities where religion, civic education, and classroom teachers serve as facilitators to strengthen the values of religious moderation, while students act as a peace makers. Specific strategies in delivering material by using quantum learning and group counselling. The learning stages of quantum learning consist of EEL Dr. C (enroll, experience, label, demonstrate, and review). Teachers collaborate for initiating the following activities: 1)Asking students to share their experiences of whether they have heard negative things about other religions and their point of view 2)Conduct discussions regarding negative stigma that students have about other religions, the teacher provides education and straightening out the misconceptions 3)Encourage students to make works of art such as poetry, writing, songs, paintings, and others about tolerance and inter-religious harmony to be displayed in student exhibitions 4)Inviting other religious leaders to do inter-faith dialogue. This program is expected to be a solution in overcoming the problem of the intolerance phenomenon in West Java in order to create inter-religious harmony and national peace.